Hypereosinophilic syndrome posttreatment with triple-negative breast cancer - Khalid A AlSaleh (Journal of Applied Hematology, 2020)
Therapy-related secondary hematological changes play a crucial role in determining the life span of an otherwise recovered cancer patient after successful treatment. Hypereosinophilic syndrome (HES) is a potentially life-threatening condition when left unmanaged. The exact etiology of HES, however, remains elusive. We report a case of an adequately treated triple-negative breast cancer patient in remission, who presented with a confirmed diagnosis of HES 2 years after her therapy. On presentation, the blood picture showed leukocytosis of 42.7 × 109/L, where 20% were eosinophils. FIP1-like-1-platelet-derived growth factor receptor-alpha fusion was observed by fluorescence in situ hybridization. The patient was treated with imatinib, according to the World Health Organization guidelines, and full remission was achieved. This is the first case of HES postchemotherapy in a solid malignancy.